Multimodal Magnetic Resonance Findings in Parkinson’s Disease With “Antecedent Essential Tremor”: A Case Series of a Large Kindred - Kong Y; Yao L; Xiao X; Chen A; Wang K; Yan H; Sun R; Liu R; Kong Q (Neuropsychiatric Disease and Treatment)
Yu Kong,1,* Lei Yao,2,* Xiangyu Xiao,2,3 Anqiang Chen,1 Kexin Wang,1 Huan Yan,4 Ran Sun,4 Ruihan Liu,5,6,* Qingxia Kong4,* 1Medical Imaging Department, Affiliated Hospital of Jining Medical University, Jining, Shandong, 272000, People’s Republic of China; 2Clinical Medical College, Jining Medical University, Jining, Shandong, 272000, People’s Republic of China; 3Cheeloo College of Medicine, Shandong University, Jinan, Shandong, 250012, People’s Republic of China; 4Department of Neurology, Affiliated Hospital of Jining Medical University, Jining, Shandong, 272029, People’s Republic of China; 5Department of Pediatrics, Affiliated Hospital of Jining Medical University, Jining, Shandong, 272029, People’s Republic of China; 6Postdoctoral Mobile Station of Shandong University of Traditional Chinese Medicine, Jinan, Shandong, 250012, People’s Republic of China*These authors contributed equally to this workCorrespondence: Qingxia Kong, Department of Neurology, Affiliated Hospital of Jining Medical University, 89 Guhuai Road, Jining, Shandong, 272000, People’s Republic of China, Email kxdqy8@sohu.com Ruihan Liu, Department of Pediatrics, Affiliated Hospital of Jining Medical University, 89 Guhuai Road, Jining, Shandong, 272000, People’s Republic of China, Email ruihanliu1987@163.comBackground: The clinical pictures of essential tremor (ET) and Parkinson’s disease (PD) are often quite mimic at the early stage, and longstanding ET may ultimately develop to PD, that is, PD with “antecedent ET”. Early diagnosis and differentiation of the two are essential for predicting disease progression and formulating individualized treatment plans. However, current approaches remain challenging. This study aimed at determining the morphological, microstructural and iron-related changes in these patients’ brains using multimodal magnetic resonance imaging (MRI).Methods: We reviewed a kindred with ET and PD with “antecedent ET” recruited at our hospital in May 2023. The clinical characteristics, genetic testing and multimodal MRI data of 16 family members were collected. Multimodal MRI analysis included structural MRI, diffusion tensor imaging (DTI) and tractography, and quantitative susceptibility mapping (QSM).Results: Two second-generation family members diagnosed PD had ET history before PD performance appeared, five third-generation family members were diagnosed with ET. Fifteen of the 16 cases had missense mutation in the EIF4G1 gene. Temporal and spatial features of morphology and iron deposition in different brain regions were heterogeneous. DTI showed that the cerebello-thalamo-motor cortical network was involved in both ET and PD cases, and the additional nigrostriatal-thalamo-motor cortical network was involved in PD cases.Conclusion: The combination of morphometric imaging, DTI and QSM could be used as an imaging biomarker for ET and PD diagnosis and could be an effective tool for longitudinal monitoring of disease progression and transformation.Keywords: magnetic resonance imaging, quantitative susceptibility mapping, diffusion tensor imaging, Parkinson’s disease, essential tremor, eukaryotic translation initiation factor 4 gamma 1